2020
DOI: 10.36547/ams.26.1.329
|View full text |Cite
|
Sign up to set email alerts
|

Austenitic Stainless Steels Manufacturing by Laser Powder Bed Fusion Technique

Abstract: In this paper we report about the possibility to process stainless steels by laser powder bed fusion (L-PBF) systems. Austenitic stainless steels are analysed showing the possibility to successfully process them, targeting different applications. In particular, it is shown that stainless steels can be successfully processed and their mechanical behaviour allow them to be put in service. Porosities inside manufactured components are extremely low and comparable to conventionally processed materials. Mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, software at the meso-dimensional level must be able to define the steel’s final properties, not only its structural and mechanical character but also its exact geometrical dimensions and shapes [ 110 ]. Nowadays, structure refinement is an attractive way to increase the strength properties of steels using the laser-powder bed fusion process [ 111 , 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, software at the meso-dimensional level must be able to define the steel’s final properties, not only its structural and mechanical character but also its exact geometrical dimensions and shapes [ 110 ]. Nowadays, structure refinement is an attractive way to increase the strength properties of steels using the laser-powder bed fusion process [ 111 , 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the tensile strength of 316L stainless steel prepared using L-PBF can range from 750 MPa to 1000 MPa, while the elongation at break can be as high as 50% [33][34][35]. Similarly, the yield strength (YS) of 316L stainless steel prepared using EBM can range from 590 MPa to 710 MPa, while the ultimate tensile strength (UTS) can be as high as 800 MPa [36,37]. In addition to the tensile properties, the fracture toughness of 316L stainless steel prepared using additive manufacturing has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Its low carbon content and good ductility help to prevent crack formation during rapid cooling [18] typical of AM technologies and no special care are needed to avoid carbides or carbon segregation related problems [34]. Moreover, due to high cost, the maraging steels are often used in the sector, such as aerospace or tool-manufacturing industries, which require the combination of complex geometries and excellent mechanical properties that can be well fulfilled by the L-PBF process [21,[35][36][37][38]. The scientific research about the production of maraging steel by L-PBF technology has been focused on the optimization of the process parameters and the condition of solution annealing and ageing heat treatments [39].…”
Section: Introductionmentioning
confidence: 99%